First-line cetuximab versus bevacizumab for RAS and BRAF wild-type metastatic colorectal cancer: a systematic review and meta-analysis - Zheng, Bobo (BMC Cancer, 2019)
BACKGROUND: A first-line biologic treatment for metastatic colorectal cancer (mCRC) is still controversial. We, therefore, performed a meta-analysis to determine the efficacy of first-line cetuximab versus bevacizumab for RAS and BRAF wild-type mCRC. METHODS: In March 2018, an electronic search of the following biomedical databases was performed: PubMed, EMBASE, Cochrane Library, ClinicalTrials.gov and Web of Knowledge. Randomized controlled trials (RCTs) and prospective or observational cohort studies (OCSs) were included. Subgroup analyses of all RCTs were performed in all outcomes. All statistical analyses were performed using RevMan software 5.3. RESULTS: Two RCTs and three OCSs, involving a total 2576 patients, were included. The meta-analysis reported that cetuximab was associated with a longer overall survival (OS) [HR 0.89, 95% CI (0.81–0.98); p = 0.02], a higher ORR [RR 1.11, 95% CI (1.03–1.19); p = 0.006], higher complete response [RR 3.21, 95% CI (1.27–8.12); p = 0.01] and a greater median depth of response than bevacizumab. However, no significant difference was observed between cetuximab and bevacizumab groups for PFS, DCR, partial response, progressive disease, curative intent metastasectomy, EORR and incidence of grade 3 or higher adverse events. In the subgroup meta-analyses of the RCTs, inconsistent results compared to the main analysis, however, were found, in the ORR, DCR and curative intent metastasectomy. CONCLUSIONS: The current evidence indicates that compared to bevacizumab treatment, cetuximab provides a clinically relevant effect in first-line treatment against mCRC, at the cost of having lower stable disease.